Propriedades físicas do solo e matéria orgânica em sistemas de plantio direto e cultivo mínimo - Laurindo, Marlene Cristina de Oliveira (2006)
The physical properties on No-Tillage (NT) and Minimum Tillage (MT) management systems were analyzed in a Rhodic Kandiudox soil from an experimental area in Foz do Iguaçu, Westerner of Paraná, whose wheat production term has been of five years under NT system. Samples were collected before wheat seeding and after its crop to record the particles densities, soil density, total porosity, textural density and organic carbon content from soil, regarding these depths: 0-5; 5-10; 10-15 and 15-20 cm. Textural density supported the answers for determining values of soil density on its limit of saturation phase as well as on its water retention limit, related to friability range and to the best aggregate stability to each analyzed depth. The NT system showed greater content of organic carbon, as well as greater soil density. The results regarding particles density increased with depth, as well as total porosity while MT system showed greater answers of porosity on upper layers, even though it contributed on reducing porosity from 10-15 and 15-20 cm layers of depths.